Sociomathematics Digital Teaching Material Design for Elementary Schools - Nurwahidin, Muhammad; Izzatika, Amrina; Hermawan, Jody Setya; Perdana, Dayu Rika; Rizqi, Yoga Fernando; Ulfah, Nufikha; Aulia, Fadilatun Nisa (Indonesian Journal of Science and Mathematics Education, 2023)
In the modern world, the approach to learning mathematics is considered a social activity because it involves interaction between teachers and students, building collaboration, and using technology to solve mathematical problems. The design of digital sociomathematics teaching materials aims to create a learning environment that is more accessible, flexible, interactive, collaborative, innovative, and efficient. This research aims to develop a socio-mathematical digital teaching material for elementary schools. The research uses development research methods, using the ADDIE development model, which consists of analysis, design, development, application, and evaluation stages. However, the current research focus is analysis, design, and development. The study data was obtained through the questionnaire. The material validation results showed 61% of the category is high and 39% is excellent. This study concludes that the instructional materials developed are employed in classroom teaching. This study suggests that future research could be directed towards evaluating the implementation of socio-mathematical digital teaching materials in primary school classrooms.